Distinct molecular profile and outcome of oligodendroglioma, IDH-mutant, 1p/19q-codeleted, and TERTp-wildtype: a grade 1 oligodendroglioma of young patients? - Nozzoli, Filippo; Rahmanzade, Ramin; Schmid, Simone; Schweizer, Leonille; Schrimpf, Daniel; Friedel, Dennis; Göbel, Kirsten; Reuss, David; Banan, Rouzbeh; Sievers, Philipp; Pusch, Stefan; Bogumil, Henri; et al. (Neuro-Oncology, 2025)
Oligodendrogliomas, characterized by isocitrate dehydrogenase (IDH) mutations and 1p/19q codeletion, often exhibit telomerase reverse transcriptase promoter (TERTp) mutations, which have been linked to telomere maintenance (TM) and tumor proliferation. Although there are a few reports on a TERTp-wildtype subset of these tumors in adolescents and young adults, the frequency, molecular characteristics, and prognostic implications of TERTp-wildtype status in oligodendrogliomas remain elusive.We retrospectively analyzed 166 IDH-mutant and 1p/19q-codeleted oligodendroglioma cases through comprehensive histopathological review and molecular analyses, including Sanger sequencing, DNA methylation profiling, and whole-exome sequencing (WES).A TERTp-wildtype status was observed in 20/166 cases (12.0%) and was significantly associated with noticeably young age (age range: 14-27, P < .001), CNS WHO grade 2 (P = .003), and the absence of additional DNA copy number variations (CNVs) beyond the pathognomonic 1p/19q codeletion (P < .001). Epigenetic profiling demonstrated TERTp-wildtype tumors shaped a distinct subgroup at the utmost periphery of TERTp-mutant oligodendrogliomas. Methylation analysis of the upstream and proximal TERTp regions revealed that, in line with the absence of genetic alterations, epigenetic regulation does not favor TERT overexpression in TERTp-wildtype oligodendrogliomas. WES showed no TM-related gene alterations in TERTp-wildtype cases. Cox regression analysis confirmed TERTp-wildtype status as an independent prognostic factor for more favorable progression-free survival (PFS) (P = .009).In conclusion, “oligodendroglioma, IDH-mutant, 1p/19q-codeleted, and TERTp-wildtype” represent a distinct molecular subgroup associated with younger age and a better clinical course compared to CNS WHO grade 2 oligodendrogliomas.
Gesehen am 28.10.2025